(NgEOLOGI^ESKAQ KARTA sREDNEJ aZII (B:s (NlIST k(B-42-(Nw(B. (N`GO(B-(NWOSTO^NAQ ^ETWERTX (B((NgOLODNAQ STEPX(B): (NmAS[TAB (B1:500 000 /s - (NaRHANGELXSKIJ(B, (Ng(B.(Ni(B.s; (NiLXIN(B, (Ni(B.(Nps; (NkOMITET PO DELAM GEOLOGII PRI snk sssrs ((NmOSKWAs (NlENINGRAD (B:s (NgOSGEOLIZDAT(B,s, 1941)
(NzAKL(B. : (NS(B. 80-81s
(NpODSTR(B. (NPRIME^(B.s
(NlIT(B.: (NS(B. 82-83s
Keywords: (NgEOLOGIQ (B- (NsREDNQQ aZIQs